PELAYANAN PERKAPALAN DI PT. PELABUHAN INDONESIA (PERSERO) I CABANG DUMAI - Fredy Farantino; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Shipping services are main services at PT. Pelabuhan Indonesia (Persero) I Cabang Dumai. The form of shipping services provided consists of pilotage and towing services that run in accordance with the Shipping Service SOP. Therefore, PT. Pelindo I Cabang Dumai must take advantage of this potential well, but in fact the income earned last year decreased compared to the previous year's revenue which identified problems in the implementation of the ship's service. This study uses a qualitative method with a descriptive approach which uses data collection techniques in the form of interviews, observations and documentation studies. The results showed that the implementation of these services, PT. Pelabuhan Indonesia (Persero) I Cabang Dumai has not been able to provide maximum service where this happens because there are still obstacles such as Human Resources which are considered to be still low and service support facilities which are considered to be poor.